Farmers' Awareness and Adoption of Digital Agricultural Technologies for Sustainable Crop Production - Shehrawat, P. S.; Arulmanikandan, B.; Singh, Sube; Aditya, (International Journal of Economic Plants, 2024)
The study was conducted at districts of Hisar and Fatehabad in the state of Haryana during the period 2022–23 to examine the farmers’ awareness and willingness to adopt digital technologies in agriculture. Digitalization may be broadly classified into two domains: its direct impact on augmenting agricultural productivity and its indirect function in enabling farmers to make better-informed and higher-quality decisions. Thus, four villages, Rajli, Ghirai, Berseen, and Majra, were randomly selected for data collection. A total of 120 farmers were selected as respondents, and their socio-personal, socio-economic, and communicational characteristics were analyzed. The findings of the study revealed that the respondents exhibited a high level of awareness about digitalization in agriculture, with a significant percentage aware of various aspects of digital technologies. They were well-informed about the potential benefits, including enhanced productivity and sustainability. In terms of adoption, a substantial number of farmers had already integrated digital technologies into their farming practices. They used digital tools for various purposes, such as online data collection, automation of farm works, nutrient management, and soil health monitoring. Overall, the study highlighted the growing awareness and adoption of digital technologies among farmers in the selected regions. These technologies have the potential to revolutionize agricultural practices and improve productivity, sustainability, and the overall quality of produce. Digitalization in agriculture is poised to play a crucial role in shaping the future of farming.